2020
DOI: 10.1177/1526924820978604
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Trapped Lung Is Associated With Increased Mortality After Orthotopic Liver Transplantation

Abstract: Introduction: Trapped lung, characterized by atelectatic lung unable to reexpand and fill the thoracic cavity due to a restricting fibrous visceral pleural peel, is occasionally seen in patients with end-stage liver disease complicated by hepatic hydrothorax. Limited data suggest that trapped lung prior to orthotopic liver transplantation may be associated with poor outcomes. Research Question: What is the clinical significance of trapped lung in patients receiving orthotopic liver transplantation? Design: We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Thus, LDH-rich fluid may suggest an inflammatory pleural effusion etiology driven by an active process rather than a simple third-spacing of fluid into body cavities [ 31 , 32 ]. Chronic inflammatory pleural effusions have been associated with worse outcomes in OLT patients, and can even lead to the development of trapped lung [ 33 ]. Our findings add to the current understanding of pleural effusion biomarkers and their ability to predict outcomes in OLT recipients, and are aligned with previously published data suggesting that elevated PF LDH is an indicator of active pleural inflammation while protein is a sign of abnormal pleural lymphatics and capillary permeability [ 15 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, LDH-rich fluid may suggest an inflammatory pleural effusion etiology driven by an active process rather than a simple third-spacing of fluid into body cavities [ 31 , 32 ]. Chronic inflammatory pleural effusions have been associated with worse outcomes in OLT patients, and can even lead to the development of trapped lung [ 33 ]. Our findings add to the current understanding of pleural effusion biomarkers and their ability to predict outcomes in OLT recipients, and are aligned with previously published data suggesting that elevated PF LDH is an indicator of active pleural inflammation while protein is a sign of abnormal pleural lymphatics and capillary permeability [ 15 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trapped lung is characterized by the atelectatic lung that is unable to expand and fill the thoracic cavity, due to a restricting fibrous visceral pleural peel. To diagnose trapped lung, drainage of the pleural space must result in both radiographic findings of a resultant pneumothorax ex-vacuo and a thickened visceral pleura [6]. The resulting fluid filled chronic pleural space, and the persistence of the fluid is solely due to hydrostatic equilibrium [7].…”
Section: Discussionmentioning
confidence: 99%
“…Hepatic hydrothorax is typically thought of as a bland, transudative fluid, resulting from the changes in the hydrostatic and oncotic pressure gradients that occur commonly with portal hypertension and cirrhosis ( 21 23 ). However, trapped lung has been described as a rare complication in patients with ESLD and hepatic hydrothorax as well ( 15 17 ). Our data reveal that pleural effusions among the TL cohort were nearly all exudative by Light’s criteria and one quarter were due to empyema.…”
Section: Discussionmentioning
confidence: 99%
“…Exudative effusions resulting from inflammatory and infectious conditions have been identified as a risk factor for the development of fibrinous change in the visceral pleura ( 13 14 ). Trapped lung is less commonly associated with ESLD, although a few small studies have shown it to be a complication of hepatic hydrothorax in a small subset of patients ( 15 17 ). When it does occur, trapped lung and pleural disease have been shown to be indicative of poor outcomes in liver transplant recipients ( 15 , 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation